Genetic Insights: Examining CNTNAP2 rs7794745 Gene Polymorphism and Its Impact on ABLLS Assessment in Middle Euphrates Children in Iraq with Autism Spectrum Disorder - AL-Safar , Safaa R. M.; AL-Zubaidy, Haydar F. S.; Alwaidh, Roaa Hameed (Journal of Contemporary Medical Sciences, 2024)
Objective: examine the effect of CNTNAP2 gene polymorphism on behavioral therapy response in Iraqi children with autism spectrum disorder using ABLLS-r. Methods: In this study, 150 samples for autism spectrum disorder were obtained from AL-SIBTEIN ACADEMY, however owing to many challenges, the final number of samples was 50 patients. Polymerase Chain Reaction-Restriction refers to a technique that combines the use of polymerase chain reaction (PCR) with restriction enzymes to amplify and analyze certain DNA sequences. Fragment Length Polymorphism (PCR-RFLP) was used to genotype the CNTNAP2 gene at rs7794745. All 25 ABLLS-R repertoires and all four primary components had their dependent parameters determined by aggregating and converting the ABLLS data to a percentage. This provided us with the proportion of finished assignments from each repertoire. Results: After correlating the genotype data (AA/AT/TT) with the behavioral therapy response as indicated by ABLLS-R, we only discovered a statistically significant difference between the frequency of AA/TT genotypes in the rs7794745 variant in patients and the social interaction domain. Conversely, the remaining 24 subdomains exhibited no discernible correlation. Conclusion: This research topic could provide significant information on targeting and categorizing which skill areas need to be developed based on genetic models' influence.